Redox Zone and Trophic State as Drivers of Methane-Oxidizing Bacterial Abundance and Community Structure in Lake Sediments - van Grinsven, Sigrid; Meier, Dimitri V.; Michel, Anja; Han, Xingguo; Schubert, Carsten J.; Lever, Mark A. (Frontiers in Environmental Science, 2022)
Eutrophication is expected to increase methane production in freshwater sediments worldwide over the coming decades. Methane-oxidizing bacteria (MOB) consume a significant fraction of this sedimentary methane, but the factors that control their distributions and activities are not understood. By combining genetic approaches (pmoA, 16S rRNA gene, metagenomics) with geochemical and sedimentological analyses, we investigate the role of trophic state, electron acceptors, oxygen (O2) and methane fluxes, and potential methylotrophic partner organisms in driving the distributions, abundances, and community compositions of MOB across five lakes in central Switzerland. Although methane fluxes were highest in the eutrophic lakes, methanotrophic abundances peaked in oxic and anoxic sediments of an oligotrophic lake. In all lakes, Type I gammaproteobacterial Methylococcaceae dominated oxic and suboxic bottom water and surface sediments, showing strong correlations with abundances of putatively methylotrophic Methylophilaceae, whereas Type II alphaproteobacterial Methylocystaceae increased in deeper, anoxic sediment layers. Methanotrophic bacteria belonging to the NC10 phylum were predominantly detected within denitrifying sediment of the oligotrophic lake, matching their presumed nitrite-dependent lifestyle. While dominant MOB taxa at the genus-level follow vertical distributions of different aerobic and anaerobic respiration reactions, trophic state at the time of sediment deposition was the best predictor of MOB community structure at the operational taxonomic unit (OTU) level. Elevated methane fluxes combined with low MOB abundances in surface sediments of eutrophic lakes, moreover, support the notion that in eutrophic lakes a major portion of sedimentary methane bypasses the biological methane filter and escapes to overlying water.